Evaluating Tech Neck: A Pilot Study Using a Self-Developed Questionnaire on Symptoms, Posture, and Preventive Measures - Brigitte Osser; Csongor Toth; Carmen Delia Nistor-Cseppento; Gyongyi Osser; Caius Calin Miuța; Iosif Ilia; Diana Carina Iovanovici; Cristina Aur; Laura Ioana Bondar (Children)
Background/Objectives: Musculoskeletal symptoms, such as neck pain, back pain, and eye strain, are prevalent in modern work environments, particularly among individuals engaged in prolonged sitting and repetitive tasks. This study aimed to explore the prevalence of these symptoms and the impact of ergonomic tool usage, break frequency, posture awareness, and proactive measures on symptom intensity and daily functioning. Methods: This cross-sectional pilot study used a self-developed questionnaire to assess the prevalence and intensity of musculoskeletal symptoms among participants aged 6–18 years. The survey collected data on ergonomic tool usage, break frequency, posture awareness, and proactive measures (such as taking breaks and seeking professional help). Symptom intensity was assessed across common musculoskeletal issues. Internal consistency was assessed using Cronbach’s Alpha. Statistical analyses, including descriptive statistics, Chi-squared tests, ANOVA, and Spearman’s correlation, were used to identify significant correlations and associations between variables. Results: A significant proportion of participants reported moderate to severe symptoms, including neck pain, back pain, and eye strain. Participants who used ergonomic tools reported significantly lower symptom intensity (<0.001). A positive correlation was found between fewer breaks and higher symptom intensity (r = 0.908, p < 0.001). Those with higher posture awareness reported lower symptom intensity (p < 0.001). Proactive measures, including regular breaks and ergonomic interventions, were perceived as effective strategies for managing symptoms. Increased symptom intensity was associated with reduced ability to perform daily activities (p < 0.001). Conclusions: The study highlights the significant role of ergonomic tools, posture awareness, and regular breaks in mitigating musculoskeletal symptoms. Proactive measures, including structured interventions, can effectively reduce symptom intensity and improve daily functioning. These findings suggest that workplace health strategies focusing on ergonomics and posture education are crucial for reducing the impact of musculoskeletal discomfort on employee well-being and productivity.